The Effect of Socio-Scientific Issue (SSI) Science Learning Based on The Decision Making Skills of Eight Grade Junior High School Student: PENGARUH PEMBELAJARAN IPA BERBASIS SOCIO-SCIENTIFIC ISSUE (SSI) TERHADAP KETERAMPILAN PENGAMBILAN KEPUTUSAN SISWA SMP KELAS VIII - Narulita, Erlia (Indonesian Journal of Science and Education, 2022)
Decision-making skills are an activity to make the best decision from several alternative solutions offered with certain considerations. This study aims to examine the effect of Socio-Scientific Issue (SSI)-based science learning on the decision-making skilss of class VIII Junior High School students. The research method used is a quasy experiment with a non-equivalent control group design. The population in this study was class VIII SMP Negeri 7 Jember in the academic year 2021/2022. The selection of research samples using purposive sampling technique obtained class VIII B as the control class and class VIII E as the experimental class. The results of the analysis used the Independent Sample T-test with a significance value og 0.041 < 0.05. In addition, based on the N-Gain test in the control class the average N-Gain is 0.4233 with moderate criteria in the less effective category, while the average N-Gain in the experimental class is 0.5568 with moderate criteria being quite effective. Based on the results of the study, it can be concluded that there is a significant effect on Socio-Scientific Issue (SSI)-based science learning on the decision-making skills of class VIII Junior High School students. Analysis with the N-Gain test shows that SSI-based science learning is included in the category of being quite effective in learning with a precentation of 56 percent. Keywords: Science Learning, Socio-Scientific Issue, Decision-making Skills